Konsep Kepemimpinan dan Pengambilan Keputusan Kepala Sekolah (Studi Kasus: MTs. Darul Ihya Ciomas) - Nesa Novrizal; Supraha, Wido; Tamam, Abas Mansur (Institut Agama Islam Sahid (INAIS) Bogor, 2024)
This study analyzes the concept of leadership and decision making of the headmaster of MTs. Darul Ihya Ciomas by using qualitative methods and interview approaches as techniques in data collection. The results obtained from this study indicate that the headmaster of MTs. Darul Ihya Ciomas has a unique and servant leadership type that focuses on protection and tends to prioritize the needs and interests of school community. In the decision-making process, the headmaster always consistently uses the family principle and mutual cooperation in order to create an inclusive and collaborative environment. These principles not only increase the sense of belonging and full responsibility among educators and education personnel but involve a more comprehensive collaboration for the achievement of effective and efficient educational goals.